Coordinate regulation of protein synthesis and messenger RNA content during growth arrest of suspension Chinese hamster ovary cells - Levis, R; McReynolds, L; Penman, S (Journal of cellular physiology, 1977)
We have found Chinese Hamster Ovary cells, cultured in suspension, are subject to growth control by serum. When suspended in medium containing 0.5% serum the cells becomes reversibly arrested in the beginning of the G1 phase of the cell cycle and can be maintained in this viable, nonproliferating state for several days. This system was used to examine the regulation of protein synthesis with growth rate. In particular, the experiments addressed the question whether mRNA content is the principal controlling factor determining the rate of protein synthesis. The rate of leucine incorporation in resting cells in low serum is 2-to 2.5-fold lower than that of cells growing in 10% serum. The steady-state number of cytoplasmic poly A (+) RNA molecules shows a proportional decrease, consistent with it being a determining factor controlling the rate of protein synthesis. Furthermore, the rate of production of poly A (+) and poly A (-) RNA appears to be regulated coordinately. Regulation of the rate of initiation of translation would result in fewer ribosomes bound per active message and/or a lower proportion of total mRNA's being active. Our measurements indicate that the fraction of cytoplasmic poly A (+) mRNA in polyribosomes and the relative degree of loading of each active poly A(+) mRNA with ribosomes is the same in resting and growing cells. Thus these cells resemble 3T6 and translational control does not appear to be an important part of the change in protein synthetic rate with teh state of growth.